Integration of transparent insulation materials into solar collector devices. (1st May 2017) - Osorio, Julian D.; Rivera-Alvarez, Alejandro; Girurugwiro, Philibert; Yang, Sam; Hovsapian, Rob; Ordonez, Juan C.
Highlights: A model to study the TIM integration into solar collector devices was developed. Effects of TIM's properties on the collectors' performance were analyzed. TIM-incorporated receivers have higher efficiencies at high absorber's temperature. Abstract: The integration of Transparent Insulation Materials (TIMs) into Flat Plate Collectors (FPCs), Parabolic Trough Collectors (PTCs), and Central Receiver (CR) collectors is studied in this paper. A general model including optical and thermal analyses is developed. The effects of TIM's properties, such as the emittance, thermal conductivity, extinction coefficient, and thickness, on the collectors' performance, are analyzed. At low absorber temperatures, performances of traditional-type collectors are relatively high. The efficiency of these collectors reduces dramatically at high temperatures due to the increment in heat losses. The incorporation of a TIM decreases thermal losses, leading to higher collectors' efficiencies at high absorber temperatures. The main goal of this study is to determine the critical operation temperature from which thermal losses reduction overcome the optical efficiency losses due to a TIM integration. In general, for high performance collectors, TIMs are characterized by low emittances and thermal conductivities, high transmittances, and low extinction coefficients.